Analisis Strategi Manajemen Biaya di PT Unilever Indonesia dalam Mengoptimalkan Efisiensi Operasional dan Meningkatkan Profitabilitas - Astika, Yunanik; Sholihah, Nikmatus; Retnowati, Eka; Fitria, Indah Ayu; Maulidia, Maulidia; Sofiyah, Sofiyah (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This research aims to analyze the cost management strategies implemented by PT Unilever Indonesia to optimize operational efficiency and enhance profitability within the competitive Fast Moving Consumer Goods (FMCG) sector.Methodology: This study employs a quantitative literature review, analyzing secondary data sourced from annual reports, journal articles, and company publications to identify patterns in PT Unilever Indonesia’s cost management practices.Results: The study finds that PT Unilever Indonesia’s cost management strategies, including supply chain optimization and technological adoption, have a positive correlation with operational efficiency and profitability.Conclusions: Cost management strategies implemented by the company have proven effective in achieving goals. Strategies that involve identifying patterns and trends over a period of time, with a focus on operational efficiency and improving financial performance.Limitations: This study relies on secondary data, which may limit insights into qualitative factors such as organizational culture that impact cost management effectiveness.Contribution: This research provides insights into effective cost management strategies for the FMCG sector, offering value to industry practitioners and academics focused on operational efficiency and profitability enhancement.